2013
DOI: 10.1152/ajpcell.00340.2012
|View full text |Cite
|
Sign up to set email alerts
|

Altered phenotypic gene expression of 10T1/2 mesenchymal cells in nonuniformly stretched PEGDA hydrogels

Abstract: Disease-related phenotype modulation of many cell types has been shown to be closely related to mechanical loading conditions; for example, vascular smooth muscle cell (SMC) phenotype shift from a mature, contractile state to a proliferative, synthetic state contributes to the formation of neointimal tissue during atherosclerosis and restenosis development and is related to SMC mechanical loading in vivo. The majority of past in vitro cell-stretching experiments have employed simplistic (uniform, uniaxial or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Like other synthetic polymers, PEG hydrogels are inert to matrix proteases, lack a fibrillar structure, and also have sub-micron pores. Consequently, encapsulated cells are confined by the surrounding polymer, which does not allow cell alignment or elongation in response to strain (Richardson et al 2013). We encapsulated U2OS osteosarcoma cells within collagen microspheres suspended within PEGDA hydrogel and investigated the morphological changes to the cells when the composite scaffold was subjected to cyclic uniaxial strain ( Figure 2).…”
Section: Engineered Tissuesmentioning
confidence: 99%
“…Like other synthetic polymers, PEG hydrogels are inert to matrix proteases, lack a fibrillar structure, and also have sub-micron pores. Consequently, encapsulated cells are confined by the surrounding polymer, which does not allow cell alignment or elongation in response to strain (Richardson et al 2013). We encapsulated U2OS osteosarcoma cells within collagen microspheres suspended within PEGDA hydrogel and investigated the morphological changes to the cells when the composite scaffold was subjected to cyclic uniaxial strain ( Figure 2).…”
Section: Engineered Tissuesmentioning
confidence: 99%
“…Third, while we simulated the effect of strain-dependent deposition, we assumed this cell response was a function of global strain and did not depend on each cell’s local orientation. Fourth, cell culture experiments have shown that mechanical loading can also modify cell proliferation (Sawaguchi et al 2010; Richardson et al 2013; Sun et al 2016). We did not include strain-induced proliferation in our model as past measurements in the supraspinatus tendon showed subtle decreases in cell density with increased levels of loading (Thomopoulos et al 2003; Galatz et al 2009).…”
Section: Discussionmentioning
confidence: 99%